DESIGN AND DEVELOPMENT OF A PIEZOELECTRIC INSOLE - Raissa Fidela Ramadhdina; Manik, Dio Ramadan; Situmorang, Yohannes Raja (Indonesian Journal of Electrical Engineering and Electronics, 2025)
This study evaluates the performance of piezoelectric materials in converting kinetic energy from footsteps into electrical energy and examines the resulting current and voltage for powering an LED. Test results indicate that body weight influences the output current and voltage of the piezoelectric circuit integrated into a shoe insole. Using a capacitor, the highest recorded current was 0.48 mA at a body weight of 80 kg. In tests with an LED, the peak current was 0.28 mA, with a voltage drop to 2.99 V at the same weight. The highest voltage output with a capacitor reached 15.50 V at 80 kg. Although the generated current and voltage were relatively small, parallel circuit configurations improved performance. Capacitors proved essential for storing energy and maintaining consistent LED illumination during walking, highlighting the potential of piezoelectric shoe insoles as practical alternative power sources.